The genetics of gastroesophageal adenocarcinoma and the use of circulating cell free DNA for disease detection and monitoring. (4th May 2017) - Openshaw, Mark R.; Richards, Catherine J.; Guttery, David S.; Shaw, Jacqueline A.; Thomas, Anne L.
ABSTRACT: Introduction : Gastroesophageal adenocarcinoma (GOA) is a frequently occurring cancer worldwide with a poor clinical outcome. Adenocarcinomas of the esophagus and gastroesophageal junction have shown a recent increase in frequency, therefore there is need to increase our understanding of GOA in order to improve our ability to detect, monitor and treat the disease. Areas covered : The authors discuss the current classification of GOA in the context of recent changes in incidence. The authors also discuss developments in the understanding of disease biology and recent discoveries from whole genome and whole exome sequencing, and studies in immunotherapy. Finally, the authors discuss the recent developments in the use of circulating tumour DNA (ctDNA). PubMed search terms were in English including 'esophageal/gastric adenocarcinoma', 'gastroesophageal junctional tumour', 'whole genome/exome sequencing', 'immunotherapy' and 'circulating tumour DNA'. Expert commentary : Shared biological and genetic changes in GOA suggest it can be investigated as a single disease entity with different molecular subtypes. A number of genes are recurrently mutated including TP53, SMAD4, PIK3CA and there are frequent somatic copy number alterations and high levels of chromosomal instability. A subset of these genetic alterations have been detected in ctDNA and may provide an important avenue of research for detecting minimal residual disease and response to chemo- and immunotherapies.